Gamma Function - 5.7 Series Expansions

From testwiki
Revision as of 16:42, 25 May 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision → (diff)
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
5.7.E1 1 Γ ( z ) = k = 1 c k z k 1 Euler-Gamma 𝑧 superscript subscript 𝑘 1 subscript 𝑐 𝑘 superscript 𝑧 𝑘 {\displaystyle{\displaystyle\frac{1}{\Gamma\left(z\right)}=\sum_{k=1}^{\infty}% c_{k}z^{k}}}
\frac{1}{\EulerGamma@{z}} = \sum_{k=1}^{\infty}c_{k}z^{k}
z > 0 𝑧 0 {\displaystyle{\displaystyle\Re z>0}}
(1)/(GAMMA(z)) = sum(c[k]*(z)^(k), k = 1..infinity)
Divide[1,Gamma[z]] == Sum[Subscript[c, k]*(z)^(k), {k, 1, Infinity}, GenerateConditions->None]
Failure Failure
Failed [50 / 50]
Result: 2.444337041-.9752791869*I
Test Values: {z = 1/2*3^(1/2)+1/2*I, c[k] = 1/2*3^(1/2)+1/2*I}

Result: 2.444337041+1.756771621*I
Test Values: {z = 1/2*3^(1/2)+1/2*I, c[k] = -1/2+1/2*I*3^(1/2)}

Result: -.287713767-.9752791869*I
Test Values: {z = 1/2*3^(1/2)+1/2*I, c[k] = 1/2-1/2*I*3^(1/2)}

Result: -.287713767+1.756771621*I
Test Values: {z = 1/2*3^(1/2)+1/2*I, c[k] = -1/2*3^(1/2)-1/2*I}

... skip entries to safe data
Failed [50 / 50]
Result: Plus[Complex[1.0783116366515544, 0.3907462172966202], Times[-1.0, NSum[Power[Power[E, Times[Complex[0, Rational[1, 6]], Pi]], Plus[1, k]]
Test Values: {k, 1, DirectedInfinity[1]}, Rule[GenerateConditions, None]]]], {Rule[z, Power[E, Times[Complex[0, Rational[1, 6]], Pi]]], Rule[Subscript[c, k], Power[E, Times[Complex[0, Rational[1, 6]], Pi]]]}

Result: Plus[Complex[1.0783116366515544, 0.3907462172966202], Times[-1.0, NSum[Times[Power[E, Times[Complex[0, Rational[2, 3]], Pi]], Power[Power[E, Times[Complex[0, Rational[1, 6]], Pi]], k]]
Test Values: {k, 1, DirectedInfinity[1]}, Rule[GenerateConditions, None]]]], {Rule[z, Power[E, Times[Complex[0, Rational[1, 6]], Pi]]], Rule[Subscript[c, k], Power[E, Times[Complex[0, Rational[2, 3]], Pi]]]}

... skip entries to safe data
5.7.E3 ln Γ ( 1 + z ) = - ln ( 1 + z ) + z ( 1 - γ ) + k = 2 ( - 1 ) k ( ζ ( k ) - 1 ) z k k Euler-Gamma 1 𝑧 1 𝑧 𝑧 1 superscript subscript 𝑘 2 superscript 1 𝑘 Riemann-zeta 𝑘 1 superscript 𝑧 𝑘 𝑘 {\displaystyle{\displaystyle\ln\Gamma\left(1+z\right)=-\ln\left(1+z\right)+z(1% -\gamma)+\sum_{k=2}^{\infty}(-1)^{k}(\zeta\left(k\right)-1)\frac{z^{k}}{k}}}
\ln@@{\EulerGamma@{1+z}} = -\ln@{1+z}+z(1-\EulerConstant)+\sum_{k=2}^{\infty}(-1)^{k}(\Riemannzeta@{k}-1)\frac{z^{k}}{k}
| z | < 2 , ( 1 + z ) > 0 formulae-sequence 𝑧 2 1 𝑧 0 {\displaystyle{\displaystyle|z|<2,\Re(1+z)>0}}
ln(GAMMA(1 + z)) = - ln(1 + z)+ z*(1 - gamma)+ sum((- 1)^(k)*(Zeta(k)- 1)*((z)^(k))/(k), k = 2..infinity)
Log[Gamma[1 + z]] == - Log[1 + z]+ z*(1 - EulerGamma)+ Sum[(- 1)^(k)*(Zeta[k]- 1)*Divide[(z)^(k),k], {k, 2, Infinity}, GenerateConditions->None]
Failure Successful Successful [Tested: 6] Successful [Tested: 6]
5.7.E4 ψ ( 1 + z ) = - γ + k = 2 ( - 1 ) k ζ ( k ) z k - 1 digamma 1 𝑧 superscript subscript 𝑘 2 superscript 1 𝑘 Riemann-zeta 𝑘 superscript 𝑧 𝑘 1 {\displaystyle{\displaystyle\psi\left(1+z\right)=-\gamma+\sum_{k=2}^{\infty}(-% 1)^{k}\zeta\left(k\right)z^{k-1}}}
\digamma@{1+z} = -\EulerConstant+\sum_{k=2}^{\infty}(-1)^{k}\Riemannzeta@{k}z^{k-1}
| z | < 1 𝑧 1 {\displaystyle{\displaystyle|z|<1}}
Psi(1 + z) = - gamma + sum((- 1)^(k)* Zeta(k)*(z)^(k - 1), k = 2..infinity)
PolyGamma[1 + z] == - EulerGamma + Sum[(- 1)^(k)* Zeta[k]*(z)^(k - 1), {k, 2, Infinity}, GenerateConditions->None]
Failure Successful Successful [Tested: 1] Successful [Tested: 1]
5.7.E5 ψ ( 1 + z ) = 1 2 z - π 2 cot ( π z ) + 1 z 2 - 1 + 1 - γ - k = 1 ( ζ ( 2 k + 1 ) - 1 ) z 2 k digamma 1 𝑧 1 2 𝑧 𝜋 2 𝜋 𝑧 1 superscript 𝑧 2 1 1 superscript subscript 𝑘 1 Riemann-zeta 2 𝑘 1 1 superscript 𝑧 2 𝑘 {\displaystyle{\displaystyle\psi\left(1+z\right)=\frac{1}{2z}-\frac{\pi}{2}% \cot\left(\pi z\right)+\frac{1}{z^{2}-1}+1-\gamma-\sum_{k=1}^{\infty}(\zeta% \left(2k+1\right)-1)z^{2k}}}
\digamma@{1+z} = \frac{1}{2z}-\frac{\pi}{2}\cot@{\pi z}+\frac{1}{z^{2}-1}+1-\EulerConstant-\sum_{k=1}^{\infty}(\Riemannzeta@{2k+1}-1)z^{2k}
| z | < 2 , z 0 formulae-sequence 𝑧 2 𝑧 0 {\displaystyle{\displaystyle|z|<2,z\neq 0}}
Psi(1 + z) = (1)/(2*z)-(Pi)/(2)*cot(Pi*z)+(1)/((z)^(2)- 1)+ 1 - gamma - sum((Zeta(2*k + 1)- 1)*(z)^(2*k), k = 1..infinity)
PolyGamma[1 + z] == Divide[1,2*z]-Divide[Pi,2]*Cot[Pi*z]+Divide[1,(z)^(2)- 1]+ 1 - EulerGamma - Sum[(Zeta[2*k + 1]- 1)*(z)^(2*k), {k, 1, Infinity}, GenerateConditions->None]
Error Successful - Successful [Tested: 6]
5.7.E6 ψ ( z ) = - γ - 1 z + k = 1 z k ( k + z ) digamma 𝑧 1 𝑧 superscript subscript 𝑘 1 𝑧 𝑘 𝑘 𝑧 {\displaystyle{\displaystyle\psi\left(z\right)=-\gamma-\frac{1}{z}+\sum_{k=1}^% {\infty}\frac{z}{k(k+z)}}}
\digamma@{z} = -\EulerConstant-\frac{1}{z}+\sum_{k=1}^{\infty}\frac{z}{k(k+z)}

Psi(z) = - gamma -(1)/(z)+ sum((z)/(k*(k + z)), k = 1..infinity)
PolyGamma[z] == - EulerGamma -Divide[1,z]+ Sum[Divide[z,k*(k + z)], {k, 1, Infinity}, GenerateConditions->None]
Failure Successful Successful [Tested: 7] Successful [Tested: 7]
5.7.E6 - γ - 1 z + k = 1 z k ( k + z ) = - γ + k = 0 ( 1 k + 1 - 1 k + z ) 1 𝑧 superscript subscript 𝑘 1 𝑧 𝑘 𝑘 𝑧 superscript subscript 𝑘 0 1 𝑘 1 1 𝑘 𝑧 {\displaystyle{\displaystyle-\gamma-\frac{1}{z}+\sum_{k=1}^{\infty}\frac{z}{k(% k+z)}=-\gamma+\sum_{k=0}^{\infty}\left(\frac{1}{k+1}-\frac{1}{k+z}\right)}}
-\EulerConstant-\frac{1}{z}+\sum_{k=1}^{\infty}\frac{z}{k(k+z)} = -\EulerConstant+\sum_{k=0}^{\infty}\left(\frac{1}{k+1}-\frac{1}{k+z}\right)

- gamma -(1)/(z)+ sum((z)/(k*(k + z)), k = 1..infinity) = - gamma + sum((1)/(k + 1)-(1)/(k + z), k = 0..infinity)
- EulerGamma -Divide[1,z]+ Sum[Divide[z,k*(k + z)], {k, 1, Infinity}, GenerateConditions->None] == - EulerGamma + Sum[Divide[1,k + 1]-Divide[1,k + z], {k, 0, Infinity}, GenerateConditions->None]
Failure Successful Successful [Tested: 7] Successful [Tested: 7]
5.7.E7 ψ ( z + 1 2 ) - ψ ( z 2 ) = 2 k = 0 ( - 1 ) k k + z digamma 𝑧 1 2 digamma 𝑧 2 2 superscript subscript 𝑘 0 superscript 1 𝑘 𝑘 𝑧 {\displaystyle{\displaystyle\psi\left(\frac{z+1}{2}\right)-\psi\left(\frac{z}{% 2}\right)=2\sum_{k=0}^{\infty}\frac{(-1)^{k}}{k+z}}}
\digamma@{\frac{z+1}{2}}-\digamma@{\frac{z}{2}} = 2\sum_{k=0}^{\infty}\frac{(-1)^{k}}{k+z}

Psi((z + 1)/(2))- Psi((z)/(2)) = 2*sum(((- 1)^(k))/(k + z), k = 0..infinity)
PolyGamma[Divide[z + 1,2]]- PolyGamma[Divide[z,2]] == 2*Sum[Divide[(- 1)^(k),k + z], {k, 0, Infinity}, GenerateConditions->None]
Successful Successful - Successful [Tested: 7]
5.7.E8 ψ ( 1 + i y ) = k = 1 y k 2 + y 2 digamma 1 imaginary-unit 𝑦 superscript subscript 𝑘 1 𝑦 superscript 𝑘 2 superscript 𝑦 2 {\displaystyle{\displaystyle\Im\psi\left(1+\mathrm{i}y\right)=\sum_{k=1}^{% \infty}\frac{y}{k^{2}+y^{2}}}}
\imagpart@@{\digamma@{1+\iunit y}} = \sum_{k=1}^{\infty}\frac{y}{k^{2}+y^{2}}

Im(Psi(1 + I*y)) = sum((y)/((k)^(2)+ (y)^(2)), k = 1..infinity)
Im[PolyGamma[1 + I*y]] == Sum[Divide[y,(k)^(2)+ (y)^(2)], {k, 1, Infinity}, GenerateConditions->None]
Failure Failure Successful [Tested: 6] Successful [Tested: 6]